Analisis Strategi STP Pada Layanan Transportasi Online (Gojek) Dalam Meningkatkan Loyalitas Konsumen : Di Wilayah Pasuruan - Putri Eka Romadhoni; Zulfa Ainun Nadzifa; Rahmatul Nur Aisyah; Salman Hood Adanie; Bintang Adi Nugraha; M. Ali Muzaki (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2025)
This study aims to determine how the Segmentation, Targeting, and Positioning (STP) strategy contributes to increasing customer loyalty towards Gojek services in the Pasuruan area. This study used a quantitative method by sending questionnaires to 99 people who actively use Gojek services. The results of the validity and reliability tests indicate that the research tool is feasible to use. According to the regression analysis, the STP strategy simultaneously contributed 71.1% to increasing customer loyalty. However, the targeting and segmentation variables did not have a significant effect partially, while positioning was proven to have the greatest influence in building customer loyalty. The results indicate that image and perceived service value are key components in retaining customers. Therefore, Gojek must strengthen its positioning strategy and reconsider how to implement segmentation and targeting to be more efficient.